Analysis of Code Mixing in Unila Zoom Photography Student Speech - Sri Kartini (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: This research was conducted with the intention of describing the utterances used by Unila photography zoom ukm students. Speeches using different languages will produce various contexts. This research was reviewed using a descriptive qualitative method. By obtaining data in the form of dialogue between Javanese-speaking students and Indonesian-speaking students, the results of this study will be carried out by describing whether the existing code mixing can make communication between speakers and interlocutors run straight or not according to the goals of the speakers and interlocutors. Keywords: speech, code mixing, university students.